Loss of PKM2 dysregulates inflammatory signaling in the infarcted murine heart - Katie C. Y. Lee; Allison L. Williams; Akitoshi Hara; Vedbar S. Khadka; Jeffrey Hayashi; Ralph V. Shohet (Physiological Reports)
Abstract Inflammation and a metabolic shift from oxidative metabolism to glycolysis are common in the ischemic heart, the latter partly controlled by pyruvate kinase (muscle, PKM). We previously identified alternative splicing promoting the PKM2 isoform after myocardial infarction (MI). We examined the role of PKM2 physiological upregulation after MI, modeled by ligation of the left anterior descending coronary artery, using global PKM2 knockout (PKM2−/−) mice. Echocardiography showed similar cardiac function between PKM2−/− and control mice after MI. However, PKM2−/− infarcted hearts had increased abundances of transcripts associated with oxidative stress and immune responses. Immunohistochemistry revealed greater abundance of macrophages in PKM2−/− hearts prior to MI, with a small increase in CD86+ macrophages in PKM2−/− infarcted hearts. Elevated baseline plasma IL‐6, IL‐1β, and C‐reactive protein, and cardiac IL‐6, 3 days post‐MI, were observed in PKM2−/− mice. Oxidative lipid products were also elevated in baseline PKM2−/− hearts, while antioxidant glutathione peroxidase 4 was reduced. Greater fibrosis was seen in PKM2−/− hearts 28 days after MI. These findings suggest Pkm2 ablation primes the heart for increased oxidative stress, inflammation, and fibrosis post‐MI. The natural upregulation of PKM2 may mitigate fibrosis by reducing oxidative stress and inflammation, highlighting its protective role in the infarcted heart.